Proximate and Sensory Properties of Dioscorea bulbifera Composite Flour Made Cookies and Cake - Induar, Sadhni; Behera, Bikash Chandra; Dubey, Debasmita; Naik, Pradeep Kumar (Asian Journal of Biological and Life Sciences)
Dioscorea bulbifera is a traditional wild tuber belongs to family Dioscoreaceae. It is not only rich in nutrients but also possesses medicinal properties. In this study an attempt has been made to produce cookies and cake from combination of wheat and Dioscorea bulbifera flour. Dioscorea bulbifera flour was incorporated with wheat flour in ratio of 25%, 50% and 75%. Composite flour made cookies and cake were examined for acceptability on the basis of biochemical and sensory parameters. Result of the study revealed that moisture, ash and fiber content gradually increases with increase in incorporation level of Dioscorea bulbifera flour (Dbf) with wheat flour at the same time as fat, carbohydrate and protein content steadily decreased. According to panelist 50% substituted cake and cookies received highest score for all the attributes. But all cookies and cake were not only obtained good score of overall acceptability but also possessed appreciable amount of nutrients.
Keywords: Cake; Composite flour; Cookies; Sensory evaluation